(untitled) (American Journal of Business Management, Economics and Banking, 2023)
This paper addressed the alignment of organizational strategy in the achievement of objectives in post pandemic era. The research advances a position on the imperatives of strategic alignment as a basis for effectively coping with related crisis and change events necessitated by the pandemic; while pursuing the objectives of the organization. Drawing on the literature review, the research identified three key areas that require focus in the alignment of organizational strategy, these include the organization’s learning, human resource development and restructuring. The paper also advanced content which highlighted the nature of corporate strategy and its related steps, including related considerations involved in the setting of objectives and the formulation of strategies. As a research paper, the investigation adopted a quantitative methodology, and a descriptive survey design. A population of 6 (4-star) hotels was also adopted in the research with referents comprising 30 management staff (5 from each hotel). In conclusion, this research affirms that corporate strategy alignment harnesses and streamlines the organizations’ resources and competencies in a way that effectively enhances its responsiveness to the changes and contextual attributes that characterize its environment in a post pandemic era.